Evaluation of blood glucose fluctuation in Japanese patients with type 1 diabetes mellitus by self-monitoring of blood glucose and continuous glucose monitoring. Issue 2 (May 2015) - Kusunoki, Yoshiki; Katsuno, Tomoyuki; Nakae, Rie; Watanabe, Kahori; Akagami, Takafumi; Ochi, Fumihiro; Tokuda, Masaru; Murai, Kazuki; Miuchi, Masayuki; Miyagawa, Jun-ichiro; Namba, Mitsuyoshi
Abstract Aims Accurate assessment of blood glucose fluctuation is essential for managing blood glucose control while avoiding hypoglycemia in patients with diabetes mellitus. In this study, blood glucose was measured by continuous glucose monitoring (CGM) in patients with type 1 diabetes mellitus (T1DM) whom self-monitoring of blood glucose (SMBG) was carried out three or more times per day, and evaluation was performed using blood glucose fluctuation parameters obtained by CGM and SMBG. Methods Twenty-nine insulin-depleted patients with T1DM were enrolled. Their blood glucose fluctuations were measured at the same time by SMBG and CGM, and the correlations were evaluated. Results Correlations were found between the following values obtained by SMBG and CGM: mean and standard deviation of blood glucose levels, average daily risk range, Morbus value and high-blood-glucose index. The hypoglycemia duration and the nocturnal hypoglycemia duration showed no correlation with any of the blood glucose fluctuation parameters obtained by SMBG. Conclusions The findings suggest that routine SMBG and glycated hemoglobin (HbA1c) measurement are sufficient for evaluation of hyperglycemia in T1DM. On the other hand, blood glucose fluctuation parameters obtained by SMBG and HbA1c have been shown to have no correlations with either hypoglycemia duration or nocturnal hypoglycemia duration.